Silver ion-Quinalphos complexes: Kinetics and NMR Studies (Journal of Academic Research, 2021)
Kinetics Studies have been carried out for the interaction between quinalphos and Ag+ at pH 4.0, 7.0 and 10.0 and temperature 25oC. Kinetics data show that Ag+ facilitated the hydrolysis of quinalphos, as the observed rate constants increased by adding silver ion. The extent of catalysis was greatly dependent on pH, as Kobs was found to increase with increasing pH.In the second part of this research, Nuclear Magnetic Resonance (NMR) is the used instrument to investigate Ag+ - quinalphos complexes. 1H and 31P NMR of quinlaphos (Q), 1H of 2-hydroxyquinoxaline (HQ), and 31P of O,O-diethyl phosphorothioic acid (PA) were recorded. 1H and 31P NMR results were consistent with the interpretation that binding between Ag+ and quinalphos occurs primarily through two positions S and N.